2014
DOI: 10.1111/jonm.12216
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to medication errors in Turkey: nurses' perspectives

Abstract: Hospital administrations should maintain adequate staffing levels. Improving medication error reporting is also imperative in order to enable nurses to document all errors and potential errors as adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
3
22
1
4
Order By: Relevance
“…The common medication errors made by nurses are wrong dose, wrong timing, wrong route, wrong rate, wrong patient, miss or bypass the administration and combination of drugs interacting with each other (Güneş et al, 2014;Antonow et al, 2000;Taxis et al, 1999;Uzun and Arslan, 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The common medication errors made by nurses are wrong dose, wrong timing, wrong route, wrong rate, wrong patient, miss or bypass the administration and combination of drugs interacting with each other (Güneş et al, 2014;Antonow et al, 2000;Taxis et al, 1999;Uzun and Arslan, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Medication administration errors are believed to result from lack of knowledge, poor communication and time constraints (Harding and Petrick, 2008;Gonzales, 2010;Güneş et al, 2014;Leape et al, 1995). Nurses must have a clear knowledge about the medications being administered, their effects, side effects and what to do in case of an adverse event since they play an important role during dispensation and administration of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Güneş et al . () concluded that enhancing the practice of reporting medication errors is paramount for enabling nurses to report all actual and potential errors.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Güneş et al . () suggested that one‐third of nurses experience interruptions while preparing medications, including answering phone calls and answering questions.…”
Section: Introductionmentioning
confidence: 99%